Work-life realities of doctors in Georgia and their impact on mental health and work-related well-being: A cross-sectional study - Elene Asanidze; Zezva Asanidze; Revaz Lordkipanidze; Manana Tsertsvadze; Aleksandre Asanidze; Nino Parunashvili; Jenaro Kristesashvili; Ana Jibladze; Swarali Yatin Chodnekar; Besik Asanidze (PLoS ONE, 2026)
Background Physicians worldwide are exposed to high occupational demands, long working hours, and emotional strain, placing them at increased risk for stress, depressive symptoms, and impaired occupational well-being. However, data describing these challenges among physicians in Georgia remain limited. Study objective This study aimed to assess the prevalence of stress and depressive symptoms among physicians in Georgia across medical specialties and to examine their associations with selected work-related and psychosocial well-being indicators, including emotional well-being, work satisfaction, sleep-related factors, and future-oriented optimism, with attention to differences by specialty, gender, and professional experience. Materials and methods A cross-sectional study was conducted using an anonymous, structured online survey administered between February 5 and May 25, 2024, in Tbilisi, Georgia. A non-probability convenience sampling method was employed. Participation was voluntary, and inclusion criteria required respondents to be 25 years or older and currently employed in either a medical or non-medical profession in Georgia. The study included 390 physicians and a control group of 240 non-medical professionals. Physicians were categorized by medical specialty. Stress and depression were assessed using the Depression, Anxiety, and Stress Scale–21 (DASS-21) and the Patient Health Questionnaire–9 (PHQ-9). Both the PHQ-9 and the DASS-21 depression subscale were included to capture depressive symptom severity using complementary, widely used screening instruments, with analyses focusing on consistency of patterns rather than direct score equivalence. Additional items captured demographic characteristics and work-related and psychosocial factors. Data were collected electronically via Microsoft Forms and analyzed using appropriate statistical methods. Analyses were primarily descriptive and bivariate. Results In unadjusted analyses, physicians reported significantly higher levels of stress and moderate-to-severe depression compared with non-medical participants ( p < 0.05). Stress levels decreased with increasing years of professional experience ( p < 0.001) and were higher among female physicians (OR = 1.7), whereas depression was more prevalent among male physicians (OR = 2.5). Married physicians reported higher stress levels than unmarried physicians ( p < 0.05). Obstetrics–gynecology, general surgery, urology, and anesthesiology exhibited the highest prevalence of stress and depression ( p < 0.05). Work-related stressors, sleep disturbances, and reduced optimism were more common among younger physicians. Conclusion Physicians in Georgia reported significantly higher levels of stress and depressive symptoms compared with non-medical professionals, with potential implications for occupational well-being and healthcare system sustainability. These findings may suggest the relevance of targeted, specialty-sensitive approaches addressing workload, organizational factors, and psychosocial support to promote physician well-being and support healthcare quality in Georgia.